The relationship between urban council characteristics, audit committee characteristics, internal audit function characteristics and timeliness of financial reporting in Zimbabwes urban councils - Tadios, Dadirai (2025)
This study examines the relationship between corporate governance characteristics and timeliness of financial reporting in Zimbabwe’s urban councils. Persistent reports of untimely release of financial statements for audit by Zimbabwe’s Urban Councils hamper scrutiny by residents on the accountability for public funds and calls into question the oversight roles of the respective governance bodies in the sector. To attract both local and foreign investment, effective oversight systems and timely reporting are required. A panel data regression analysis using a census of the urban councils registered in the country according to the country’s Urban Councils (2006) Act covering the period 2012 to 2021 was conducted. The governing board characteristics analysed consist of its size, political party composition and political competition. Furthermore, the Audit Committee independence, size, meeting frequency, chair financial expertise and financial expertise in addition to the Internal Audit Function size, independence, sourcing arrangements, competence, and management support were evaluated. Based on the agency theory of corporate governance, the study used two panel data multiple regression models for analysis. Model 1 tests the relationship between the identified Urban council, Audit Committee, and Internal audit function characteristics with Financial Statement Submission Delay while model 2 employs the Audit Delay to test the same variables. Statistical results demonstrated that in Zimbabwe’s urban councils only political party composition, audit committee meeting frequency, audit committee financial expertise, audit committee size, standalone budget for the internal audit function, possession of professional qualifications by internal auditors as well as the proportion of internal audit recommendations implemented by management were significantly influencing timeliness of financial reporting for both models. The study provides players in the urban councils’ corporate governance system, including the central government, parliament and residents, with insights into governance issues requiring their attention. It is recommended that these stakeholders influence timely financial reporting in the urban councils by promoting adoption of the key variables identified as significant in the study